Determining spatially-resolved thermal radiation from non-intrusive measurements of soot properties. (October 2022) - Escudero, F.; Demarco, R.; Cruz, J.J.; Verdugo, I.; Carvajal, G.; Olivares, G.; Valenzuela, F.; Han, D.; Lin, H.; Fuentes, A.
Abstract: A procedure is presented that uses estimations of soot volume fraction and temperature fields to (i) calculate the spatially-resolved radiative intensity emitted from soot, and (ii) model the incident radiative power released from the flame by soot particles on a surface. The procedure is validated using both experimental and simulated data obtained from a canonical laminar diffusion flame about 5 cm high. First, estimations of soot volume fraction and temperature derived from non-intrusive experimental measurements are used to calculate the reference soot radiative intensity and to simulate the signals captured by radiometers located at different positions relative to the flame. Then, simulated radiometer signals are processed using different viewfactor methodologies to retrieve the values of integrated soot flame radiation, which are then compared to the reference intensity obtained from soot volume fraction and temperature by solving the radiative transfer equation. Results show that point-source methods accurately estimate the reference intensity (within 2% of error) when using simulated signals from radiometers positioned 7 and 10 cm from the flame axis and up to three times the flame height. Moreover, the double cylinder model accurately estimates flame radiation from measurements performed above three times the flame height. Highlights: Fields of radiative power determined from soot volume fraction and temperature. Spatially-resolved radiative power used to simulate and compare radiometer signals. Assessment of radiant fraction established from different viewfactor methodologies. Simulated and experimental signals deviations increase radiative information.